Characterization of Ar-Rassafeh Badyieh area (Area-2), Syria by using the airborne gamma-ray spectrometric and fractal modelling techniques - ASFAHANI, Jamal (Contributions to Geophysics and Geodesy, 2019)
The available aerial gamma-ray spectrometric data of Ar-Rassafeh Badyieh area (Area-2) are used herein for geological interpretations and mapping purposes. Those data are interpreted by the concentration-number (C-N) fractal modelling technique, with the use of log-log graphs. According to C-N model, different radioactive ranges of TC, eU, eTh, and K have been isolated. Those ranges are thereafter used to characterize thelithological outcrops in the study area. The radioactive signatures of all the outcrops in Area-2 have been discussed and documented through establishing the C-N maps of TC, eU, eTh, and K, and benefiting of the available geological map. The C-N fractal modelling technique proves its efficacy, where radioactive and lithological boundaries of outcrops are in concordance. The case study presented in this paper shows the importance and the role of airborne gamma-ray spectrometric and fractal modelling techniques to support thegeological mapping and the interpretations in geological context, particularly when the study region is rugged and difficult to be accessed.